The Effectiveness of Inquiry-Group Based Blended Learning Management System on High School Physics of High School Students of North Sumatera-Indonesia - Motlan; Mihardi, Satria; Sinuraya, Jurubahasa (Advances in Social Sciences Research Journal, 2022)
The merging of these systems is based on the effectiveness and efficiency of the learning and teaching processes. Offline teaching which is combined with online makes the teaching and learning processes more effective in the way the students have more effective discussions and enable students to collaborate to present the few topics being discussed. This type of learning and teaching will provide flexibility for schools to adapt to government policies to prevent students from being too crowded by dividing students into offline and online groups. Blended learning will also make learning more effective and efficient where students can study more independently as well as have access to learning material resources. This system can deepen the mastery of material through more exercise by exposing to learning resources that are available on the internet which are unlimited. Misunderstood blended learning and teaching models and they think of blended learning as a model of learning. Several studies use blended learning with conventional teaching methods. Some works have also combined blended learning with various models of teaching. A choice of a suitable model of learning on a specific topic is also required. It depends on the learning outcomes. Different models of learning have different direct and nurturant effects. This work tries to look at A compact blended learning mode that was used in this work the Flip model with 50% Face to Face and 50% online alternating. This is required to split the students into two groups by reducing the number of students present at school at the same time. The target of this research is to see the effectiveness of an inquiry-group based blended learning management system (IGBLMS). Analysis of the results of the study was carried out using N-gain analysis and non-parametric statistics. Non-parametric statistics are used to analyze in detail the specific effects of processes and outcomes. This analysis will show in detail the direct impact of the research design. The conclusion that can be reached is that the effectiveness of blended learning carried out in supporting learning activities is effective learning even with moderate criteria. This makes a breakthrough in learning to be able to support learning activities without reducing the existence of learning with pre-existing systems.